Pengaruh Presepsi Harga, Kualitas Pelayanan Dan Lokasi Terhadap Kepuasan Pelanggan Batik Danar Hadi Semarang - Edy Suryawardana; Sugeng Riyanto; Citra Rizkiana; Kamalina Din Jannah (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this study was to analyze the effect of perceived price, service quality and location on customer satisfaction at Batik Danar Hadi Branch Semarang. The hypothesis of this study is the perception of price, service quality and location have a positive effect on customer satisfaction at Batik Danar Hadi Semarang. The number of samples in this study were 76 people. Then the method of collecting data through questionnaires and data analysis using SPSS which includes validity test, reliability test, classical assumption test, multiple linear regression analysis, F test, and hypothesis testing using t test and R2. The results showed that the independent variable, namely price perception, had no effect on customer satisfaction. This is evidenced by the value of t arithmetic is smaller than t table that is -0.977 < 1.667 with a significant value of 0.332 > 0.05 (not significant). Service quality has a positive effect on customer satisfaction. This is evidenced by the value of t arithmetic is greater than t table that is 3.592 > 1.667 with a significant value of 0.001 < 0.05 (significant). Location has positif effect on customer satisfaction. This is evidenced by the value of t arithmetic is bigger than t table that is 1.725 > 1.667 with a significant value of 0.039 < 0.05 (significant). Based on the value of the coefficient of determination, the test results show the adjusted r square value of 0.638, this means that changes in the customer satisfaction variable of 63.8% can be explained by the independent variables of price perception, service quality, and location. Meanwhile, 36.2% was influenced by other variables not examined.